2022
DOI: 10.1016/j.celrep.2022.110313
|View full text |Cite
|
Sign up to set email alerts
|

SoxD genes are required for adult neural stem cell activation

Abstract: Highlights d Neural stem cell transition from quiescence to activation requires Sox5 and Sox6 d Loss of Sox5 or Sox6 decreases adult neurogenesis in the dentate gyrus d Transcription of neural stem cell activator Ascl1 is modulated by Sox5 and Sox6 d Environmental enrichment boosts stem cell activation, which is hampered by Sox5 loss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…Among the regions with increased distal accessibility in HepLPC-P3, SOX6 and SOX21 were enriched. SOX6 and SOX21 are highly expressed in stem/progenitor cells and are required for stem cell activation and maintenance [ 31 , 32 ]. Two embryonic-developmental genes, GRHL2 and PRDM10 , were found to be enriched.…”
Section: Resultsmentioning
confidence: 99%
“…Among the regions with increased distal accessibility in HepLPC-P3, SOX6 and SOX21 were enriched. SOX6 and SOX21 are highly expressed in stem/progenitor cells and are required for stem cell activation and maintenance [ 31 , 32 ]. Two embryonic-developmental genes, GRHL2 and PRDM10 , were found to be enriched.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies showed that the self-renewal and/or differentiation capacities of NSCs and NPCs in neurogenic regions of the adult brain are regulated by several SOX genes: SOX2, SOX21, SOX9, SOX4 and SOX11 [63][64][65]88,109,110]. Furthermore, a recent study in the hippocampus showed the critical role of SOX5 and SOX6 in the transition of NSCs from quiescence to activation [89].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…qNSCs-quiescent neural stem cells, NPCs-neural progenitor cells, DG-dentate gyrus, CA1-cornu ammonis 1, CA3cornu ammonis 3. The scheme is based on the previously reported publications [16,19,22,23,89].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…More specifically, PNS enhanced the expression of bromodomain containing genes Atad2 (ATPase family AAA domain containing 2) and Brd8 (bromodomain containing 8) that have been shown to be involved in ESR1 (estrogen receptor alpha) mediated transcriptional regulation of cell proliferation in cancer cell lines [58][59][60] . PNS increased expression levels of Wnt pathway modulators Ezh2, Tcf4, Ephb2, and Sox2, which play important roles in sustaining cell stemness and promoting cell proliferations [61][62][63][64][65] . The Wnt and the estrogen signaling pathways are tightly associated with MAPK3/1 signaling to stimulate tumorigensis 26,66,67 .…”
Section: Fig5c)mentioning
confidence: 99%